Syntheses of Bis‐Triazole Linked Carbohydrate Based Macrocycles and Their Applications for Accelerating Copper Sulfate Mediated Click Reaction. Issue 6 (3rd January 2019) - Chen, Anji; Samankumara, Lalith P.; Dodlapati, Sanjeeva; Wang, Dan; Adhikari, Surya; Wang, Guijun
Abstract : Macrocyclic compounds play an important role in many research fields including drug discovery and development, bioorganic chemistry, and materials sciences. Carbohydrate‐based macrocycles are important compounds with unique structures and many potential applications. In this study, we have designed and synthesized a series of 1, 2, 3‐triazole linked and pyranose embedded macrocycles in short steps through the copper (I) catalyzed azide and alkyne cycloaddition reactions (CuAACs). Eight non‐symmetrical glucosamine based and bis‐triazole linked macrocycles have been synthesized starting from the readily available N‐ acetyl‐d ‐glucosamine. These triazole‐linked glycomacrocycles showed remarkable reaction rate accelerations for CuSO4 mediated azide and alkyne cycloaddition reactions in aqueous mixtures. Several azides including a sugar azide, which react sluggishly with alkynes, have been accelerated with the synthesized macrocycles. The benzoylated macrocycles with three methylene linkage at anomeric positions were the most effective among the eight macrocycles. Abstract : Eight glucosamine based 1, 2, 3‐triazole linked macrocycles were synthesized starting from the readily available N‐ acetyl‐d ‐glucosamine. These bis‐triazole‐linked glycomacrocycles showed remarkable rate acceleration for CuSO4 mediated azide and alkyne cycloaddition reactions in aqueous solutions.